Impact of investment in intermediate waste management facilities (Sunter and Bantargebang) on the economy of DKI Jakarta Province - Aleknaek Martua (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2022)
Until now, the waste problem in DKI Jakarta Province is an unresolved matter. This is still the task of the local government. In carrying out the mandate of regional autonomy, DKI Jakarta Province is currently active in promoting sustainable development, especially dealing with waste. Green investment management is currently the government's focus with a waste management facility project. In total, the investment required to build a waste management facility between Sunter and Bantargebang is Rp.5.84 trillion. This study examines the impact of the waste management facility project on economic output and employment in DKI Jakarta Province. The analysis used is input-output analysis by entering the stimulus amount of investment to the infrastructure category sector. The waste management facility project has been able to mobilize key sectors, including the electricity sector, construction sector, land transportation sector, and information and communication services sector. The impact of the project was able to encourage additional output in a number of sectors with an accumulation of Rp. 9.40 trillion. Meanwhile, the absorption of labor due to the addition of output in a number of sectors is projected to absorb 9,195 workers.